Bionic composite membrane for thermal management of human body and preparation method and application of bionic composite membrane

Through electrospinning technology, phase change materials are encapsulated and surface treatment of gallium indium alloy was performed to prepare a bionic composite film with high photothermal conversion efficiency and excellent energy storage performance, which solves the leakage of existing phase change materials during phase change process. and the problem of low energy storage efficiency.

CN119465510APending Publication Date: 2025-02-18NANJING FORESTRY UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411399356.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing phase change materials are prone to leakage during the phase change process, low energy storage efficiency, and difficult to achieve personalized temperature regulation.

Method used

Using the preparation method of bionic composite film, polylactic acid, gallium indium alloy and paraffin are encapsulated into nanofiber films through electrospinning technology, and gallium indium alloy is processed through ball milling to form a surface bead morphology to improve photothermal conversion efficiency.

Benefits of technology

It improves the photothermal conversion efficiency of the composite film, provides excellent energy storage and thermal insulation performance, enhances the absorption capacity of sunlight, and realizes personalized temperature regulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465510A_ABST
    Figure CN119465510A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of material synthesis, and particularly relates to a bionic composite membrane for human body thermal management and a preparation method and application thereof. The method comprises the following steps: S1, dissolving polylactic acid and a pretreated gallium-indium alloy in an organic solvent A to obtain a first solution; dissolving a phase change material in an organic solvent B to obtain a second solution; dissolving polyvinyl alcohol in an organic solvent C as a third solution; s2, performing electrostatic spinning by taking the first solution as an outer layer solution, the second solution as a first inner layer solution and the third solution as a second inner layer solution to prepare a nanofiber membrane; s3, soaking the nanofiber membrane in deionized water, and then freeze-drying to obtain the bionic composite membrane. A surface bead-string shape is formed on the polylactic acid PLA fiber, so that the sunlight absorption capacity of the composite film is effectively improved, and the photothermal conversion effect is enhanced; meanwhile, the interfacial effect is eliminated through pretreatment, and the strength of the fiber membrane is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material synthesis, and in particular relates to a bionic composite film for human body thermal management and a preparation method and application thereof. Background Art

[0002] Maintaining thermal comfort of the human body in various environments is the key to ensuring the normal progress of human production activities. When the ambient temperature drops, the temperature of the human body mainly depends on the clothes worn, as well as the combustion of air conditioners and fossil fuels. However, with the extensive use of air conditioners and fossil fuels, people are facing increasingly severe energy crises and global warming problems. Under the requirements of energy saving and consumption reduction, enhanced warmth retention, etc., individual thermal management that can widely regulate the human microenvironment and achieve precise heating of non-overall living spaces has become a current research hotspot. The use of renewable energy as a substitute for fossil fuels is crucial to solving energy and environmental problems. Among them, solar energy has the largest reserves, is pollution-free, and has a wide range of sources. It is the most promising substitute for fossil fuels. People hope to use solar energy and the fabric itself to create a comfortable environment, thereby replacing the current energy-intensive indoor air conditioners and realizing personalized temperature regulation of flexible wearable devices.

[0003] Phase change materials, as energy storage media, can undergo phase changes at nearly constant temperature and store or release energy at the same time, achieving efficient energy utilization and thus reducing CO 2 Phase change material is the core of phase change heat storage technology and one of the most critical components in the phase change heat storage system. However, it is prone to leakage during the phase change process, has low energy storage efficiency, and is difficult to achieve personalized temperature regulation. Summary of the invention

[0004] In view of the above problems existing in the prior art, the present invention provides a bionic composite film for human body thermal management and a preparation method and application thereof, which can improve the light-to-heat conversion efficiency of the composite film and provide excellent energy storage and thermal insulation performance.

[0005] To achieve the above object, the technical solution provided by the present invention is as follows:

[0006] In a first aspect, the present application provides a method for preparing a bionic composite film for human body thermal management, comprising the following steps:

[0007] S1: dissolving polylactic acid and the pretreated gallium-indium alloy in an organic solvent A to obtain a first solution; dissolving a phase change material in an organic solvent B to obtain a second solution; and dissolving polyvinyl alcohol in an organic solvent C to obtain a third solution;

[0008] S2: using the first solution as the outer layer solution, the second solution as the first inner layer solution, and the third solution as the second inner layer solution to prepare a nanofiber membrane by electrospinning;

[0009] S3: Soaking the nanofiber membrane in deionized water, and then freeze-drying it to obtain the bionic composite membrane.

[0010] Optionally, the preparation of the pretreated gallium-indium alloy comprises the following steps: adding the gallium-indium alloy to a ball mill, adding Tween 80 and thiomalic acid thereto, and ball milling in an organic solvent D for 3-8 h, wherein the organic solvent D is tetrahydrofuran, N-methylpyrrolidone, dimethyl sulfoxide or N,N-dimethylformamide.

[0011] Optionally, the organic solvent A is dichloromethane and N,N-dimethylformamide, and the volume ratio of dichloromethane to N,N-dimethylformamide is (4-6):2.

[0012] Optionally, the ball milling time is 6 h.

[0013] Optionally, the advancing speed of the outer layer solution is 2-6 mL / h, the advancing speed of the outer layer solution in the electrospinning is 2-5 times that of the first inner layer, and the discharge speed of the outer layer solution is 2-5 times that of the second inner layer.

[0014] Optionally, S3 specifically includes: first drying the nanofiber membrane in a vacuum oven at 40-60° C.; then ultrasonically immersing the nanofiber membrane in deionized water to remove the polyvinyl alcohol, and finally freeze-drying the nanofiber membrane.

[0015] Optionally, the mass ratio of polylactic acid to gallium-indium alloy raw material is (2-3):1.

[0016] Optionally, the phase change material includes paraffin, the organic solvent B is a non-polar solvent, and the organic solvent is gasoline, kerosene, toluene or xylene.

[0017] Optionally, the volume ratio of the phase change material to the solvent B is 1:(1.5-3).

[0018] Optionally, the mass volume ratio of polyvinyl alcohol to organic solvent C is (2-5): 100 g / mL, and the organic solvent C is dimethyl sulfoxide.

[0019] Optionally, the paraffin wax is modified in advance as follows: the paraffin wax is mixed with dodecane and tridecane under stirring at 30-45°C, and then cooled at 15-25°C.

[0020] Optionally, the mass ratio of the added amount of thiomalic acid to the gallium-indium alloy is (0.05-0.2):1, and the mass ratio of the added amount of Tween 80 to the gallium-indium alloy is (0.3-0.6):1.

[0021] In a second aspect, the present application also provides a bionic composite membrane for human thermal management, which is prepared by the preparation method described in the first aspect.

[0022] In a third aspect, the present application also provides an application of the bionic composite film described in the second aspect in human thermal management.

[0023] Compared with the prior art, this application has at least the following beneficial effects:

[0024] (1) The present invention utilizes a ball milling process to perform surface treatment on the gallium-indium alloy to remove its surface oxide layer. In order to prevent the oxidation problem of the gallium-indium alloy, Tween 80 and thiomalic acid are added to the system before ball milling to prepare a stable pre-treated gallium-indium alloy, which is beneficial to forming a surface beaded morphology on the polylactic acid (PLA) fiber, effectively improving the composite film's ability to absorb sunlight and enhancing the photothermal conversion effect. At the same time, the pretreatment eliminates the interface effect and enhances the strength of the fiber membrane.

[0025] (2) Through multi-fluid spinning, paraffin is efficiently encapsulated, which avoids leakage of phase change materials and improves energy storage properties. The internal hollow morphology is created to give the material thermal insulation properties, which improves wearing comfort and has broad application prospects in the field of human thermal management materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the morphology test results of the pretreated gallium-indium alloy in Example 1, wherein a is an electron microscope image; b is a particle size distribution diagram;

[0027] Figure 2 This is an electron microscope image of the biomimetic composite membrane prepared in Example 1;

[0028] Figure 3 A schematic diagram of the temperature and time variation cycle of the biomimetic composite membrane prepared in Example 1 and Example 2;

[0029] Figure 4 This is a schematic diagram of thermal imaging recorded by an infrared camera when the bionic composite film prepared in Example 1 is transferred from light to shade;

[0030] Figure 5 This is a schematic diagram of thermal imaging recorded by an infrared camera after the bionic composite film prepared in Example 1 is worn on a human body indoors. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0032] The experimental methods used in the embodiments of the present invention are conventional methods unless otherwise specified.

[0033] The reagents and materials used in this example can all be purchased conventionally. The quantitative experiments involved in the examples were repeated at least three times, and the results were averaged.

[0034] Source of raw materials:

[0035] Gallium-indium alloy: purchased from Shenyang Jiabei Trading Co., Ltd.; its composition is: gallium 75wt%, indium 25wt%.

[0036] Paraffin wax was purchased from Dongguan Shengbang Polymer Materials Co., Ltd.

[0037] Example 1

[0038] A method for preparing a bionic composite film for human body thermal management, the specific steps are as follows:

[0039] Step 1: Add 15 ml of tetrahydrofuran (THF) to a 100 ml zirconia jar containing 75 zirconia balls (including 60 zirconia balls with a diameter of 6 mm and 15 zirconia balls with a diameter of 10 mm). Then, add 2 g of gallium-indium alloy raw material, 0.2 g of thiomalic acid and 1 g of Tween 80 according to a certain ratio. Use a QM-3SPO4 planetary ball mill to run at a speed of 480 rpm for 6 hours to obtain a pretreated gallium-indium alloy.

[0040] 0.8 g of polylactic acid (PLA) particles were dissolved in a mixed solution of 5 ml of dichloromethane and 2 ml of N,N-dimethylformamide, and 3 ml of pretreated gallium-indium alloy was added thereto in a ratio of 7:3 between the gallium-indium alloy raw material and the polylactic acid to prepare a first solution;

[0041] Mixing kerosene and paraffin in a volume ratio of 2:1 to obtain a second solution;

[0042] Polyvinyl alcohol and dimethyl sulfoxide were mixed in a ratio of 3 g:100 mL to obtain a third solution.

[0043] Step 2: Add the first solution, the second solution and the third solution into the syringe respectively, use a three-fluid electrospinning needle with a specification of 15G / 25G-25G for spinning, and use a cylindrical metal roller to collect the nanofibers, the roller diameter is 8cm and the width is 20cm; the electrospinning parameters are set as follows: the applied voltage is 22 kV, the outer layer solution propulsion speed is 4mL / h, the two inner layer solution propulsion speeds are 1.3mL / h, and the distance between the needle tip of the syringe and the collection roller is kept at 15cm. After 120 minutes of electrospinning, the nanofiber fabric with uniform thickness is collected as the nanofiber membrane.

[0044] Step 3: Dry the nanofiber membrane in a vacuum oven at 40°C for 24 hours, then place it in deionized water for ultrasonic treatment and soak it for 48 hours to remove the polyvinyl alcohol (PVA) inside, and then freeze-dry it for 48 hours to finally obtain a bionic composite membrane with a composite morphology.

[0045] Example 2

[0046] Step 1: dissolving 0.8 g of polylactic acid PLA particles in a mixed solution of 5 ml of dichloromethane and 2 ml of N,N-dimethylformamide to obtain a first solution;

[0047] Kerosene and paraffin were mixed in a volume ratio of 2:1 to obtain a second solution.

[0048] Step 2: Add the first solution and the second solution into the syringe respectively, use a 15G / 25G-25G dual-fluid electrospinning needle for spinning, and use a cylindrical metal roller to collect the nanofibers, the roller diameter is 8cm, and the width is 20cm; the electrospinning parameters are set as follows: the applied voltage is 22 kV, the outer solution advancing speed is 4mL / h, the inner solution advancing speed is 1.3mL / h, and the distance between the needle tip of the syringe and the collecting roller is kept at 15cm. After 120 minutes of electrospinning, the collected nanofiber fabric with uniform thickness is the nanofiber membrane.

[0049] Step 3: Dry the nanofiber membrane in a vacuum oven at 40°C for 24 hours to finally obtain a bionic composite membrane.

[0050] The light-to-heat conversion efficiency and energy storage characteristics of the phase change thin film materials obtained in the above-mentioned Examples 1 and 2 are shown in Table 1. It can be seen that the performance of the bionic composite film obtained in this application is significantly improved compared with that in Example 2.

[0051] Table 1 Comparison of composite membrane performance

[0052] sample Photothermal conversion efficiency (%) Enthalpy (J / g) Example 1 53.6% 89.7 Example 2 42.3% 76.1

[0053] Figure 1 This is an electron microscope image of the morphology of the pretreated gallium-indium alloy. Figure 1 It can be seen from a that the particle size of the gallium-indium alloy is relatively uniform after ball milling. Figure 1 The particle size distribution diagram given in b shows that the average size of the gallium-indium alloy is greater than 2 μm, and a clear beaded morphology can be formed on the fiber (such as Figure 2 ), the experiment found that when the ball milling time is too short, the particle size is too large, which reduces the strength of the fiber membrane. When the ball milling time is too long, a beaded morphology is slowly formed on the fiber, which is not conducive to improving the photothermal conversion efficiency. The best time for ball milling is 6 hours, at which time both higher fiber strength and photothermal conversion can be obtained.

[0054] from Figure 2 From the SEM image of the cross section, it can be observed that the solid fibers are encapsulated with paraffin wax and most of the solid fibers have a hollow morphology. This result shows that we have successfully prepared a composite morphology with surface gallium-indium alloy beads and a hollow interior.

[0055] Figure 3 a. Figure 3b is a temperature and time variation cycle diagram of the bionic composite membranes prepared in Example 1 and Example 2, respectively. Under the xenon lamp simulating 100 mW / cm² solar radiation, the temperature of the bionic composite membrane gradually increases with time, reaches saturation within a certain period of time, and then turns off the xenon lamp to start cooling. Both embodiments have a plateau period during the cooling process. This is because the paraffin melts and absorbs heat during the heating process, and then crystallizes and releases heat during the cooling process. By comparison, it can be seen that the saturation temperature of Example 1 is slightly higher than that of Example 2, and the heat release platform is more obvious. The beaded morphology on the surface of the gallium-indium alloy brings strong light absorption and excellent photothermal conversion performance to the bionic composite membrane, which improves the energy storage efficiency of the bionic composite membrane. 10 photothermal cycle experiments show that it has excellent photothermal cycle stability.

[0056] Figure 4 The thermal imaging image of the biomimetic composite film obtained in Example 1 during actual wearing, recorded by an infrared camera, is shown. Under sunlight (outdoor temperature 30°C), the temperature of the biomimetic composite film quickly rises to 47°C, much higher than the skin surface temperature of 36.6°C, demonstrating its rapid photothermal response. Figure 4 a. Move the human body from the light to the shade (about 15℃), record the moment of transfer as time 0, and then test the surface temperature of the composite film after different transfer times (the blank control group does not add the composite film, and the body surface temperature is tested). The results are as follows: Figure 4 As shown in b, c, and d, due to the disappearance of light, the temperature of the blank control group dropped rapidly, while when the bionic composite membrane was set, the energy storage material in the membrane released energy to provide warmth to the human body. Therefore, the surface temperature of the bionic composite membrane dropped slowly at the beginning, and then the temperature could be maintained stable for a period of time. After testing for ten minutes, the surface temperature of the membrane material of the part with the bionic composite membrane was still maintained at about 34.5℃.

[0057] In addition, the thermal insulation performance of the bionic composite film obtained in Example 1 was tested (at this time, there was no energy stored in the bionic composite film). After the human body temperature was balanced (body surface 35°C) in an indoor environment (about 25°C), the bionic composite film was worn on the human body at time 0 (compared with the non-wearing group, the non-wearing group tested the body surface temperature). The surface temperature of the bionic composite film after different times was tested. The results are as follows: Figure 5 As shown, due to the hollow morphology, a large amount of air is filled inside the fiber, and the bionic composite membrane can prevent the body's own heat from being dissipated, bringing a warming effect (the surface temperature of the composite membrane is lower than the body surface temperature of the control group, which shows that the composite membrane blocks the heat from being dissipated into the air to a certain extent). The phase change bionic composite membrane with a gallium-indium alloy surface beaded and a hollow composite morphology prepared by the present invention can provide continuous warmth to the human body in outdoor tests and effectively prevent the loss of its own heat.

[0058] Example 3

[0059] By mixing paraffin with dodecane and tridecane in different proportions to obtain modified paraffin, the phase transition temperature of paraffin PW can be changed to achieve wide phase transition temperature regulation and meet temperature personalization requirements. In this embodiment, modified paraffin is used as a phase change material for preparing a composite film.

[0060] Take 0.5g of raw paraffin and place it in an oven to melt, and take 1g of dodecane and 0.5g of tridecane and preheat them to 35°C. After preheating, the melted paraffin is heated in a 37°C water bath and mixed with dodecane and tridecane, and stirred for 1 hour. The mixture is then cooled to room temperature to obtain a modified paraffin, and its phase change temperature range is finally measured by DSC to be 20-30°C. The phase change temperature range of the phase change material can be regulated by the method in the embodiment.

Claims

1. A method for preparing a bionic composite film for human body thermal management, characterized in that: The steps include: S1: dissolving polylactic acid and the pretreated gallium-indium alloy in an organic solvent A to obtain a first solution; dissolving a phase change material in an organic solvent B to obtain a second solution; and dissolving polyvinyl alcohol in an organic solvent C to obtain a third solution; S2: using the first solution as the outer layer solution, the second solution as the first inner layer solution, and the third solution as the second inner layer solution to prepare a nanofiber membrane by electrospinning; S3: Soaking the nanofiber membrane in deionized water, and then freeze-drying it to obtain the bionic composite membrane.

2. The method for preparing the bionic composite film for human body thermal management according to claim 1, characterized in that: The preparation of the pretreated gallium-indium alloy comprises the following steps: adding the gallium-indium alloy into a ball mill, adding Tween 80 and thiomalic acid into the ball mill, and ball milling in an organic solvent D for 3-8 hours.

3. The method for preparing the bionic composite film for human body thermal management according to claim 1, characterized in that: The advancing speed of the outer layer solution is 2-6 mL / h. The advancing speed of the outer layer solution in the electrospinning is 2-5 times that of the first inner layer, and the discharge speed of the outer layer solution is 2-5 times that of the second inner layer.

4. The method for preparing the bionic composite film for human body thermal management according to claim 1, characterized in that: S3 specifically includes: firstly drying the nanofiber membrane in a vacuum oven at 40-60°C; then immersing the nanofiber membrane in deionized water by ultrasonic to remove the polyvinyl alcohol; and finally freeze-drying the nanofiber membrane.

5. The method for preparing the bionic composite film for human body thermal management according to claim 2, characterized in that: The mass dosage ratio of polylactic acid to gallium-indium alloy raw material is (2-3):

1.

6. The method for preparing the bionic composite film for human body thermal management according to claim 1, characterized in that: The phase change material includes paraffin, and the organic solvent B is a non-polar solvent.

7. The method for preparing the bionic composite film for human body thermal management according to claim 6, characterized in that: The paraffin wax is modified in advance as follows: the paraffin wax is mixed with dodecane and tridecane under stirring at 30-45°C, and then cooled at 15-25°C.

8. The method for preparing the bionic composite film for human body thermal management according to claim 2, characterized in that: The mass ratio of the added amount of thiomalic acid to the gallium-indium alloy is (0.05-0.2):1, and the mass ratio of the added amount of Tween 80 to the gallium-indium alloy is (0.3-0.6):

1.

9. A bionic composite membrane for human thermal management, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 8.

10. Application of the bionic composite film described in claim 9 in human body thermal management.

Citation Information

Patent Citations

  • Method for preparing phase-change heat-storage fiber membrane with core-shell structure by utilizing coaxial electrospinning technology

    CN108570766A

  • Sized and coated photo-thermal phase change composite yarn and preparation method thereof

    CN113529421A

  • Efficient energy convergence and storage bionic structure and preparation method and application thereof

    CN114851642A

  • Polylactic acid-gallium indium alloy adhesive material based on electrostatic spinning as well as preparation and application of polylactic acid-gallium indium alloy adhesive material

    CN116657327A

  • Fiber with heat storage function and preparation process thereof

    CN117089951A